Enhancing Students' Collaboration Skills Through Tic-Tac-Toe in Think Pair Share Strategy of Global Warming Concepts - Hidayah, Nurul; Fatmaryanti, Siska Desy; Ashari, Ashari (Jurnal Ilmiah Pendidikan Fisika, 2024)
Developing students' collaboration skills is important in today's 21st-century education. Global warming is one of the important issues in physics learning that is interesting to study. This study aims to improve students' collaboration skills by integrating Tic-Tac-Toe game with Think-Pair-Share (TPS) strategy in physics learning on the concept of global warming. This research adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) conducted at MA Al Iman Bulus Purworejo, starting with a limited trial involving 5 students and continuing to implementation with 34 students. The research instruments included validation sheets for developing student worksheets, observation sheets for collaboration skills, and student response questionnaires to collect comprehensive data on the effectiveness of the intervention. The data analysis results showed that the electronic worksheet's validity obtained a score of 3.86 with a valid category, and the practicality of the electronic worksheet based on the student response questionnaire obtained an average of 84.1% with a very practical category. The research findings revealed that integrating Tic Tac-Toe with TPS strategy can improve students' collaboration skills from the ibservation score of 44.5 to 87.3. The N-gain was 0.8, which is included in the high category. Using games in learning with cooperative learning strategies such as TPS accompanied by worksheets is proven to provide students with an interactive and fun approach to mastering collaboration skills and global warming concepts.